Recent Insights into the Synthesis of Oligosaccharides from Escherichia coli: Review - Sharma, Anjali; Rabha, Padmashri; Panchadhayee, Rajib (Current Organic Chemistry, 2025)
The development of effective therapeutics to control the infections of drug-resistant bacterial strains is the thrust area in medicinal chemistry. The glycoconjugate containing O-antigenic oligosaccharide and a carrier protein linked through a linker can develop an antigen against gram-negative bacteria like Escherichia coli (E. coli), Shigella, Providencia, and Salmonella. Therefore, the chemical synthesis of glycoconjugate vaccine candidates against these bacterial strains is a growing demand of modern-day research. The synthesis of carbohydrate parts that are oligosaccharides is the most challenging. Significant developments in oligosaccharide synthesis have occurred over the past few decades. This review will focus on the chemical synthesis of different complex oligosaccharides related to different strains of E. coli. This review concludes with a summary of synthetic developments and prospects.
Keywords: vaccines